Mitochondria tether protein trash to rejuvenate cellular environments - Mogk, Axel; Bukau, Bernd (Cell, 2014)
Protein damage segregates asymmetrically in dividing yeast cells, rejuvenating daughters at the expense of mother cells. Zhou et al. now show that newly synthesized proteins are particularly prone to aggregation and describe a mechanism that tethers aggregated proteins to mitochondria. This association constrains aggregate mobility, effectively retaining and sorting toxic aggregates away from younger cells.